Design and evaluation of mutilayer sound absorber - Chaw, Zhi Xin (2021)
Sound pollution has always been a big problem faced by everyone during their daily lives, especially for those who have the special needs to work under quiet environment. There are a lot of research that has been done on experimenting different design of sound absorber since the invention of it from long ago. While on the other hand, as a newly introduced fabrication method, 3D printing has been used frequently for rapid prototyping as it has much more flexibility to produce a prototype with much lower cost and time required. The main aim of this project is to evaluate the effect of the combination of Micro-perforated panel (MPP), Cartesian porous panel and Hexagonal porous panel toward its sound absorption ability. These panels are aligned as 2 layer sound absorber panels with varying inter-layer distance, combination between panels and sequences. Throughout this project, the sound absorption peak varies depending on the combinations of panels as well as its sequence. Generally, the combination panels which include the Hexagonal porous panel would have a better sound absorption ability compared to the other combinations, except when MPP is placed at the second layer. While among this combinations, the combinations between Cartesian and Hexagonal porous panel would have the highest peak of sound absorption coefficient at round α ≈ 1. However, the frequency range of the absorption peaks would shift slightly toward the higher or low frequency regions when the combination among the 3 printed panel aligned at the 1st and 2nd layer have changed. Based on the study, the current proposal is only effective for the frequency range above 1100Hz. In addition, the varying inter-layer distance has also contribute to the shifting of absorption peak of the combination panels. When the inter-layer distance between each layer increases from 0 mm to 40 mm, the absorption peak would shift slightly towards the lower frequency range while increasing in sound absorption coefficient, reaching its optimum at inter-layer distance = 40 mm. These finding would benefit the tuning the room acoustics to tackle the specific frequency range as a dead room is not healthy to human being when a high absorptive materials across a wide frequency range is used.